Evaluation of Human Resources (HR) and Its Implications for Service Quality at the SMKN 2 Bandung Library - Firdausy, Rachmelya Salsabila; Hadiapurwa, Angga; Wulandari, Yayu (Inkunabula: Journal of Library Science and Islamic Information, 2025)
This study aims to evaluate the performance and capacity of human resources and their impact on the quality of services provided at the library of SMKN 2 Bandung by employing the Balanced Scorecard model. A descriptive qualitative method was adopted, utilizing the Balanced Scorecard approach, which includes four perspectives: financial, customer satisfaction, internal processes, and learning and growth. Data were collected through interviews with three groups of informants: the principal, librarians (including the head librarian and staff), and library users (teachers and students). The findings were triangulated through direct observation and document analysis. The results indicate that the library is staffed by only two librarians, both of whom lack relevant educational backgrounds, leading to excessive workloads and inefficiencies in core services, particularly cataloging, circulation, and reference. Despite limited funding, the school consistently provides training programs to enhance librarians’ competencies. From the customer perspective, most users report receiving adequate assistance, although the services are not yet optimal. The study concludes that human resource inadequacies have a direct and significant impact on the quality of library services in vocational high schools.AbstrakPenelitian ini bertujuan untuk mengevaluasi kinerja dan kapasitas sumber daya manusia serta pengaruhnya terhadap kualitas layanan yang diberikan di Perpustakaan SMKN 2 Bandung dengan menggunakan pendekatan model Balanced Scoredcard. Metodologi yang diterapkan adalah kualitatif deskriptif menggunakan pendekatan Balanced Scorecard, yang mencakup empat sudut pandang: aspek finansial, kepuasan pelanggan, proses internal, serta aspek pembelajaran dan perkembangan. Data diperoleh melalui wawancara dengan tiga kelompok informan, yaitu kepala sekolah, pustakawan yang mencakup kepala dan staf, serta pemustaka yang terdiri atas guru dan siswa. Hasil data diperkuat dengan observasi dan dokumentasi. Temuan dari penelitian menunjukkan bahwa perpustakaan hanya memiliki dua staf pustakawan yang berasal dari latar belakang yang tidak sesuai, yang berakibat pada beban kerja yang berlebihan dan ketidakefisienan dalam layanan, terutama dalam proses katalogisasi, sirkulasi, dan referensi. Meskipun anggaran terbatas, pihak sekolah tetap menyelenggarakan pelatihan rutin untuk meningkatkan keterampilan pustakawan. Dari perspektif pelanggan, sebagian besar pengguna merasa cukup mendapatkan bantuan meskipun layanan yang tersedia belum maksimal. Penelitian ini menyimpulkan bahwa ketidakidealan dalam sumber daya manusia berpengaruh langsung terhadap kualitas layanan perpustakaan di Sekolah Menengah Kejuruan.